Cultural self-representation and heritage practice of community museums: two case studies - Tan, Yan Ni (Nanyang Technological University, 2022)
This study begins with an exploration on the roles of community museum and its relationship with the community. On the intention of refining the definition of community museum, this study attempts to use comparison of two case studies, Sapan Puloh Mini Museum (SPMM) and Peck San Theng Heritage Gallery (PSTHG), to investigate how community museum embrace the needs of local contexts, responding not only to communities but also socio-political environments. Qualitative case study method is utilized in data collection, and a contextual framework to compare and analyse them. The findings have shaded lights on the functions and repositioning of community museum. In both case studies, the community museums are facing struggle or dilemma in the sustainability of their culture due to cultural assimilation and globalisation. It is at this conjuncture when the cultures’ representations are called into question, this study tries to trace how and whether cultural expressions are related to cultural redevelopment and transformation. On each community museum analysis is placed on the impact of: site; collections; curatorial approach; and community. From the results, both case studies share commonality in setting boundaries to manipulate their cultural territories, albeit in different approaches. Two community museum models, taking in account influential factors that could be generalized for a community museum, are constructed for the reference of other heritage-making projects in the future.